A randomised controlled trial investigating the effects of administering a non‐steroidal anti‐inflammatory drug to beef calves assisted at birth and risk factors associated with passive immunity, health, and growth. Issue 1 (19th October 2019) - Pearson, Jennifer M; Pajor, Edward; Campbell, John; Levy, Michel; Caulkett, Nigel; Windeyer, M Claire
Abstract : Background: The objectives of this study were to investigate the impact of pain mitigation at birth to assisted beef calves and determine the risk factors associated with transfer of passive immunity (TPI), health, and growth. Methods: Two hundred and thirty cow–calf pairs requiring calving assistance were enrolled. Calves were randomised to receive meloxicam (0.5 mg/kg) or an equivalent volume of placebo subcutaneously at birth. Calf blood samples were collected between one and seven days of age to determine serum immunoglobulin (IgG) concentration. Colostrum intake, treatment for disease, mortality, and weaning weights were recorded. Multilevel linear or logistic regression models were used to determine the effects of meloxicam and to identify risk factors. Results: There was no effect of meloxicam on serum IgG concentrations, average daily gain (ADG), or risk of inadequate TPI (serum IgG concentration <24 g/l), treatment for disease, or mortality (P>0.05). Bottle or tube feeding calves were associated with decreased serum IgG concentrations (P=0.01) compared with nursing. Calves with an incomplete tongue withdrawal reflex had higher odds of being treated for disease compared with those with complete withdrawal (P=0.009). Being born meconium‐stained and having decreased serum IgG concentrations were associated with an increased risk of mortality (P=0.03). Being born of a mature cow, having a higher birth weight, and increased serum IgG concentrations were associated with greater ADG to weaning (P<0.05). Conclusion: Vigour assessment at birth along with good colostrum management may be important to improve TPI and health in high‐risk calves such as those assisted at birth.